PENGAJARAN SENI TARI DI PAUD/TK SYAWAL - Maghfirah; Hilda Zahra Lubis; Salsabilah; Salsabila Siregar (JIP: Jurnal Ilmu Pendidikan, 2025)
Dance is one of the essential tools in supporting the development of early childhood, especially in motor, social, emotional, and creative aspects. This study aims to examine the dance teaching methods applied at PAUD/TK Syawal and their influence on children's development. This topic was chosen due to the lack of integration of dance education in many early childhood institutions. The research used a descriptive qualitative approach with data collected through participatory observation, semi-structured interviews, and documentation. The research subjects consisted of two dance teachers, several students, and parents involved in learning activities. The results showed that teachers at PAUD/TK Syawal taught dance creatively using familiar children’s songs, simple movements, and rhythmic musical instruments. These activities were proven to enhance children’s activeness, confidence, movement coordination, and expressive ability. This study highlights the importance of dance as an integral part of early childhood learning that is not only entertaining but also educational. In conclusion, appropriate dance teaching methods have significant potential in shaping children's character and holistic skills.